Policy learning in collaborative government: A framework for adaptive and resilient public policy - Martikalini, Citra (Edelweiss Applied Science and Technology, 2024)
Collaborative government has emerged as a critical approach in addressing complex public challenges that demand adaptive and resilient policies. This study explores the concept of policy learning within collaborative government settings, emphasizing its potential to foster innovation and flexibility in public administration. By conducting a comprehensive literature review, the research identifies the key dimensions and mechanisms that support adaptive and resilient policymaking. The findings suggest that effective policy learning requires robust stakeholder engagement, dynamic knowledge-sharing platforms, and iterative evaluation processes. Furthermore, the study introduces a conceptual framework that integrates collaborative governance practices with adaptive policy principles. This framework offers a systematic approach to enhancing policy resilience in the face of uncertainty and rapid societal changes. The discussion highlights the theoretical implications for governance studies and the practical applications for policymakers. By addressing the gap between collaborative governance and policy learning, this research contributes to advancing the discourse on resilient public policies. Future studies are encouraged to empirically test the proposed framework and explore its applicability in diverse governance contexts.